Shyness and self-consistency and congruence among Chinese adolescents: mediating role of social comparison orientation and moderating role of self-focused attention - Yu, Yang; Sun, Hong (Frontiers in Psychology, 2024)
During the critical period of personality shaping and self-development, adolescents face unique challenges and opportunities. This study, based on Cognitive-Behavioral Theory, explored the relationship between shyness and self-consistency and congruence (hereinafter referred to as SCC), as well as its underlying mechanisms. Through a questionnaire survey on shyness, social comparison orientation, self-focused attention, and SCC among 984 adolescents, the results revealed that (1) Adolescent shyness negatively predicted SCC. (2) Social comparison orientation partially mediated the relationship between shyness and SCC. (3) Self-focused attention moderated the direct pathway of this mediation process, where a high level of self-focused attention exacerbated the negative impact of shyness on SCC. These findings offered a new perspective on understanding SCC and underscored the importance of addressing the information processing mechanisms of social comparison orientation and self-focused attention among shy adolescents in interventions aimed at promoting their psychological harmony and healthy growth.